EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN LANJUT USIA DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Gultom, Roby; Aminah Harahap (JIFI (Jurnal Ilmiah Farmasi Imelda), 2021)
Hypertension is called the "silent killer" which is a risk factor for heart disease, stroke and kidney failure. High blood pressure that can not protect properly will increase the mortality and morbidity. Elderly patients aged ? 60 years, most of them already have hypertension and even have experienced the risk factors caused by hypertension. The goal of therapy is not to exacerbate organ damage and reduce mortality and improve patient quality so that evaluation is necessary, especially for the selection of antihypertensive drugs. This study aims to meet the suitability of the types of antihypertensive drugs given to elderly patients at the General Hospital of Imelda Pekerja Indonesia Medan with the standard of hypertension treatment. Research data collection was carried out in a retrospective manner in the period January-April 2020. Data were analyzed using the SPSS 21, JNC VIII (2016) method. There were 9 patients (28.1%), the use of antihypertensive drugs in elderly patients who did not comply with the standard recommendations for hypertension therapy and 23 patients (71.9%) who used antihypertensive drugs in accordance with JNC VIII standards.